ANALISIS PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MATA PELAJARAN PELAKSANAAN DAN PENGAWASAN KONSTRUKSI DI SEKOLAH MENENGAH KEJURUAN - Ananda Surya Lesmana (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Problem-based learning (PBL) has become a major focus in technical and vocational education, especially in the context of Construction Implementation and Supervision subjects in Vocational High Schools. This article aims to conduct an in-depth analysis of the literature examining the use of PBL methods in the mentioned context. Through a comprehensive literature review, I explore various aspects, including implementation approaches, benefits gained, as well as challenges faced in applying PBL in construction learning. In addition, I also identified current trends or media in the use of PBL and considered its implications for learning in Schools. The results of this study not only provide valuable insights for educators and administrators in Vocational High Schools, but also serve as a foundation for further research in an effort to improve the effectiveness of engineering learning at the Vocational High School level, as well as enrich academic discussions on innovative learning approaches.